Communique: Workshop on the development of proposed pathways for adoption and domestication of priority actions and other policy instruments for SADC Member States - AU-IBAR (AU-IBAR, 2022)
The report highlights the pathways for the adoption and domestication of regional instruments by SADC Member States.
Keywords: Live2Africa; Regional Value Chains; SADC